Five new species of the leafhopper genus Thagria Melichar (Hemiptera: Cicadellidae: Coelidiinae) from China - Wang, Xiu-Dan; Zhang, Ya-Lin (Zootaxa, 2017)
Five new species of genus Thagria are described, illustrated and photographed: T. gansuensis sp. nov., T. menglana sp. nov., T. melanoloma sp. nov., T. incurvata sp. nov., and T. crena sp. nov.